Role of A-Kinase Anchoring Protein Phosphorylation in Alcohol-Induced Liver Injury and Hepatic Stellate Cell Activation - Ramani, Komal; Tomasi, Maria Lauda; Berlind, Joshua; Mavila, Nirmala; Sun, Zhaoli (The American journal of pathology, 2018)
Alcoholic liver injury is associated with hepatic stellate cell (HSC) activation. A-kinase anchoring protein 12 (AKAP12) scaffolds protein kinase C and cyclin-D1, which is regulated by its phosphorylation, and spatiotemporally controls cell proliferation, invasiveness, and chemotaxis. HSC activation induces AKAP12 expression, but the role of AKAP12's scaffolding activity in liver function is unknown. Because AKAP12 phosphorylation is enhanced in ethanol-treated HSCs, we examined AKAP12's scaffolding functions in alcohol-mediated HSC activation and liver injury. AKAP12 expression, interaction, and phosphorylation were assayed in in vitro and in vivo ethanol models and human subjects by real-time PCR, coimmunoprecipitation, immunoblotting, and phosphorylated proteomics/Phos-tag. Ethanol induced AKAP12 phosphorylation in the liver and in primary HSCs, but not in hepatocytes. AKAP12's scaffolding activity for protein kinase C/cyclin-D1 decreased in ethanol-treated HSCs but not hepatocytes. AKAP12 negatively regulated HSC activation, which was reversed by ethanol-mediated AKAP12 phosphorylation. AKAP12 interacted with heat shock protein 47 (HSP47), which chaperones collagen and induces its secretion. Ethanol inhibited AKAP12-HSP47 and induced HSP47-collagen interaction. Ethanol-induced phosphorylated AKAP12 was unable to bind to HSP47 compared with its unphosphorylated counterpart, thereby proving that ethanol-mediated phosphorylation of AKAP12 inhibited the HSP47-AKAP12 scaffold. Silencing AKAP12 facilitated the chaperoning of collagen by HSP47. Hence, AKAP12 scaffolds HSP47 and regulates collagen-HSP47 interaction. Ethanol quenches AKAP12's scaffolding activity through phosphorylation and facilitates HSC activation.